Relationship recovery: an integrated conceptual framework - Haque, A. K. M. Ahasanul; Rabbanee, Fazlul Kabir; Yasmin, Sanoara (The International Journal Research Publications, 2012)
Customer relationship management not only focuses on acquiring new customers and maintaining relationship with them but also emphasizes on winning back the defected customers. Understanding why the customers get defected and how to restore their trust and re-acquire relationship with them are of immense importance for the managers as well as academicians. Based on literature survey, this paper focuses on how to restore customer trust and relationship after the occurrence of a relationship failure event. It provides insights into the nature of relational problems, focuses on causes of relationship failure, and antecedents of customers’ exit decision from current relationship with the company after a transgression. It suggests a conceptual framework incorporating three key aspects of relationship recovery efforts – affective, functional and informational, that may lead the company to prove its trustworthiness to the customers after a transgression, which directs the company to win back relationships with them. Subsequently, propositions regarding different components of the model are presented in the paper, which are aiming towards reacquiring relationship with the defected customers.